If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(Z+4)=-3(Z+5)
We move all terms to the left:
(Z+4)-(-3(Z+5))=0
We get rid of parentheses
Z-(-3(Z+5))+4=0
We calculate terms in parentheses: -(-3(Z+5)), so:We get rid of parentheses
-3(Z+5)
We multiply parentheses
-3Z-15
Back to the equation:
-(-3Z-15)
Z+3Z+15+4=0
We add all the numbers together, and all the variables
4Z+19=0
We move all terms containing Z to the left, all other terms to the right
4Z=-19
Z=-19/4
Z=-4+3/4
| 11x8=11x+8 | | -3.5z=14 | | 5y^2=-30y | | (2x-27)+x=180 | | 10/x+5=11 | | 2/3(9w-24)=-10 | | 12z2=34z−12 | | (x+40)=(3x-20)=180 | | 3x=-3-9 | | |5x|-10=20 | | 11=b+7 | | 15.847=2x(102/149) | | (x/x^2-25)-(x+6/x^2-5x)=-10/x^2+5x | | (x+40)=(3x-20)=90 | | X+8/x=4x-5/3 | | 10n-185=-86 | | -9+9=-g-7 | | 13=2/(+x) | | 2x+1=x+3=180 | | 3(-2x+1)=x–7x+7 | | -12=12r+36 | | 4/3+1/3=-5y-5 | | 3.5x-8.62=1.5x-2.38 | | -94=p/59 | | 2|3x+8|=12 | | 13(×-7)=5x-131 | | −5(4y−9)−y=−2(y−3) | | 13=-2/(+x) | | 63=3-3x | | (x-2)(3x+5)=x(x-2) | | 6(5y+1)=18y | | 2/3h+11-1/3h=6 |